2013
DOI: 10.1007/s11033-013-2558-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and combined genotypes of MC4R and POU1F1 genes on two production traits in Langshan chicken

Abstract: The objective of this study was to analyze the effects of single and combined genotypes of MC4R and POU1F1 genes in Chinese well-known indigenous chicken (Langshan chicken) population. Genetic variants within MC4R gene and POU1F1 gene were screened through PCR-SSCP and DNA sequencing methods. A C/T mutation at nt 944 in MC4R gene (NC_006089.2:g. 944C>T) and a G/A mutation at nt 3109 in POU1F1 gene (NC_006088.2:g. 3109 G>A) were identified. Associations between the mutations of the two genes with two production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…This role has been shown to be evolutionarily conserved in vertebrates (Andersone et al, 2016). Allele and genotype distribution of MC4R gene have been described by many researchers in monogastric and polygastric animal such as in chicken (Yan et al, 2013), pig (Piorkoswka et al, 2010Davoli et al, 2012;Zhang et al, 2017), sheep (Song et al, 2014;Wang et al, 2015), cattle (Huang et al, 2010;Liu et al, 2010;Maharani et al, 2018) and buffalo (Deng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This role has been shown to be evolutionarily conserved in vertebrates (Andersone et al, 2016). Allele and genotype distribution of MC4R gene have been described by many researchers in monogastric and polygastric animal such as in chicken (Yan et al, 2013), pig (Piorkoswka et al, 2010Davoli et al, 2012;Zhang et al, 2017), sheep (Song et al, 2014;Wang et al, 2015), cattle (Huang et al, 2010;Liu et al, 2010;Maharani et al, 2018) and buffalo (Deng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The 1426G>A mutation in the MC4R gene has been associated with feed intake, growth, fatness, and carcass composition in porcine individuals (Van den Maagdenberg et al 2007;Piórkowska et al, 2010). Similarly, many single nucleotide polymorphisms (SNPs) have been identified that are associated with body weight, carcass weight, and back fat thickness in cattle (Liu et al, 2010), sheep (Song et al, 2012), and chicken (Yan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Hu sheep, four MC4R SNPs in the 3 -UTR of MC4R were also identified (Song et al, 2012). Numerous studies also have revealed that SNPs of MC4R gene were associated with physical and qualitative traits in chicken (Huo Mingdong and Hui, 2006;Yan et al, 2013) and rabbits (Jiang et al, 2008). The role of MC4R in feed intake and obesity in many livestock species suggests that it may be an important genetic marker for the growthrelated traits in the sheep.…”
Section: Introductionmentioning
confidence: 99%